On the Complexity of Aggressive Behavior: Contextual and Individual Factors in the Taylor Aggression Paradigm - Weidler, Carmen; Habel, Ute; Hüpen, Philippa; Akkoc, Dilsa; Schneider, Frank; Blendy, Julie A.; Wagels, Lisa (Frontiers in Psychiatry, 2019)
As many paths lead to aggression, understanding which situations and which person-specific traits facilitate or impede aggressive behavior is crucial. Provocation is among one of the most frequently reported predictors of aggressive behavior. However, it remains unclear, whether the reaction to provocation is universal across different forms of aggression and whether individuals differ in their reactivity to such signals. Using the Taylor Aggression Paradigm (TAP), we investigated the influence of individual and contextual factors on physical and non-physical aggression in healthy men and women. The impact of trait aggression, sex, provocation and the success of a competition against a fictitious opponent on aggressive behavior was examined in three different versions of the TAP. While equal provocation and punishment modalities were used in the first two versions, monetary deductions in the first and heat stimuli in the second study, the third experiment used non-physical provocation to trigger physical punishment. Trial-by-trial analyses revealed that provocation, independent of its specific nature, is a strong predictor for aggressive behavior, especially in highly aggressive participants. While women initially showed less aggression than men, sex differences were diminished under prolonged, increasing provocation when provocation and punishment modality were identical. Only when modalities diverged, women, compared to men, were more hesitant to punish their opponent. These results thus extend evidence that women show lower levels of aggression under low provocation. However, high levels of provocation have similar effects on males’ and females’ reactive aggressive behavior across different forms of aggression. When competing for money, losing against the fictitious opponent was functioning as an additional provocative signal stimulating aggressive responses. Differences in aggressive responding have to be interpreted in the context of the specific type of provocation and aggression that is investigated since these modalities are shown to interact with individual characteristics.